2020
DOI: 10.31729/jnma.5288
|View full text |Cite
|
Sign up to set email alerts
|

Blood Donation Practice among Undergraduate Students in a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Voluntary blood donation is a reliable source of increasing the demand for blood transfusion. Medical students are the potential pool of blood donors. This study aims to find the prevalence of blood donation practice among medical students of a medical college in Nepal. Methods: This is a descriptive cross-sectional study conducted in a medical college of Nepal among students studying from the first year to final year MBBS. Ethical approval was obtained from the Institutional Review Committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…Similarly, a study conducted at Arsi University and Adama Science and Technology University found that health science students have higher blood donation practices as compared to nonhealth science students (27.2% versus 22.8%). 27 However, the practice of health science students' blood donation in the present study is in contrast to a study carried out in South India 10.75%, 27 Spain, 32.62%, 32 Nepal, 22.2%, 33 Saudi Arabia 30.1% 34 and Northeast Ethiopia 12.4%. 35 This might be due to the difference in the implementation of blood donation campaigns and different barriers to blood donation including being unqualified for blood donation and fear of contracting diseases.…”
Section: Discussioncontrasting
confidence: 87%
“…Similarly, a study conducted at Arsi University and Adama Science and Technology University found that health science students have higher blood donation practices as compared to nonhealth science students (27.2% versus 22.8%). 27 However, the practice of health science students' blood donation in the present study is in contrast to a study carried out in South India 10.75%, 27 Spain, 32.62%, 32 Nepal, 22.2%, 33 Saudi Arabia 30.1% 34 and Northeast Ethiopia 12.4%. 35 This might be due to the difference in the implementation of blood donation campaigns and different barriers to blood donation including being unqualified for blood donation and fear of contracting diseases.…”
Section: Discussioncontrasting
confidence: 87%
“…Another study carried out by Dawadi P et al also found that blood donation practice was more among final year students 15 (35.71%) and the least among first year 3 (8.57%). 14 It was found in the present study that 19 (16.1%), 34 (32.7%) and 55 (44.4%) students who had donated blood belonged to the first year, the second year, and final year while a study done by James T et al showed 9.1%, 37.9% and 42.4% of students who have donated blood belonged to the first year, second year and a final year respectively. 16 The present study showed that there was a significant difference in attitude between male and female students while in contrast, the study done by Suresh S et al showed that there was no statistically significant difference in attitudes between males and females (p-value = 0.17).…”
Section: Figure2: Extent Of Correct Knowledge On Blood Donation Among the Study Participants Discussionsupporting
confidence: 37%
“…The study done by Chopra D et al found that 72 % male and 28% female students had donated blood and the difference was statistically significant (p-value-0.00). 10 Dawadi P et al 14 showed that out of 126 males, 28 (22.2%) and out of 59 females, 13 (22.03%) were found to have donated blood previously. The present study showed that there was a significant association between blood donation with male students exceeding female students in actual blood donation.…”
Section: Figure2: Extent Of Correct Knowledge On Blood Donation Among the Study Participants Discussionmentioning
confidence: 99%
See 1 more Smart Citation